Assessment of riverbank filtration performance for climatic change and a growing population - Abd-Elaty, Ismail; Kuriqi, Alban; Ganayem, Hala M.; Ahmed, Ashraf; Saleh, Osama K.; Garrote, Luis (Frontiers in Environmental Science, 2023)
Riverbank filtration (RBF) consists of green drinking water production in many regions and is used as a pre-treatment phase. This study investigates the performance of the RBF in the Nile delta, Egypt, for climate change and population growth scenarios of 2030, 2040, and 2050. This study presents a new method for predicting the sharing of riverbanks considering three cases: i) the river stage controlling the water levels in the river, ii) increasing RBF pumping, and iii) changing the groundwater levels. This last scenario is achieved by changing the general head in the MODFLOW model. The results showed that RBF sharing (RBFS) is a proportion of the river leakage inflow, in which the decrease of the river stage due to the influence of climate change reduced the river leakage inflow and RBFS. In addition, increasing RBF pumping, decreasing RBF pumping, and lowering the groundwater levels due to the increase in the future drinking water pumping for the population growth increased the river leakage inflow and RBFS. Finally, combining the three cases decreased RBFS in the coming years of 2030, 2040, and 2050, respectively, due to more groundwater sharing than the river inflow. The results show that the water budget is a good tool to investigate RBFS compared with MT3D results. This technique can reduce the cost of water quality collection and analysis; moreover, it will help with the estimation of RBF and save time compared with solute transport modeling.